Males, the Wrongly Neglected Partners of the Biologically Unprecedented Male–Female Interaction of Schistosomes - Lu, Zhigang; Spänig, Sebastian; Weth, Oliver; Grevelding, Christoph G. (Frontiers in Genetics, 2019)
Schistosomes are the only platyhelminths that have evolved separate sexes, and they exhibit a unique reproductive biology because the female's sexual maturation depends on a constant pairing-contact with the male. In the female, pairing leads to gonad differentiation, which is associated with substantial morphological changes, and controls among others the expression of gonad-associated genes. In the male, no morphological changes have been observed following pairing, although first data indicated an effect of pairing on gene transcription. Comprehensive transcriptomic approaches have revealed an unexpected high number of genes that are differentially transcribed in the male following pairing. Their identities suggest roles for the male that are not restricted to feeding and enhanced muscular power to transport paired female and, as assumed before, to induce its sexual maturation by one “magic” factor. Instead, a more complex picture emerges in which both partners live in a reciprocal sender-recipient relationship that not only affect the gonads of both genders but may also involve tactile stimuli, TGFβ-signaling, nutritional parts, and neuronal processes including neuropeptides and GPCR signaling. This review provides a summary of transcriptomics including an overview about pairing-dependently expressed genes in schistosome males. This may stimulate further research in understanding the role of the male as recipient of female signals upon pairing, the male´s “capacitation”, and its subsequent competence as a sender of information. The latter process, finally, transforms a sexually immature, autonomous female without completely developed gonads into a sexually mature, partially non-autonomous female with fully differentiated gonads and enormous egg-production capacity.